Thermodynamic, exergoeconomic, and exergoenvironmental analysis of a combined cooling and power system for natural gas-biomass dual fuel gas turbine waste heat recovery. (15th April 2023) - Ren, Jie; Qian, Zuoqin; Fei, Chunguang; Lu, Ding; Zou, Yincai; Xu, Chen; Liu, Lu
Abstract: Integrating biomass energy into existing fossil fuel power plants is a practical way to solve the current energy shortages and environmental problems considering system feasibility and economic benefits. In this work, a novel combined cooling and power (CCP) system is proposed for waste heat recovery of a natural gas-biomass dual fuel gas turbine (DFGT) based on the organic Rankine cycle (ORC) and absorption refrigeration cycle (ARC). Comprehensive thermodynamic, exergoeconomic, and exergoenvironmental performance and parametric analysis of this system are performed. Results show that under the design condition, thermal efficiency, exergy efficiency, levelized cost of exergy (LCOE), and levelized environmental impact of exergy (LEIOE) of the system are 68.88%, 42.10%, and 21.16 /GJ, and 5208.82 mPts/GJ, respectively. Among all the components, combustion chamber has the highest exergy destruction rate. The parametric analysis indicates that the thermal and exergy efficiencies rise by increasing the gas turbine inlet temperature (GTIT) and ORC turbine inlet pressure or by decreasing the preheated air temperature (PAT) and exhaust gas outlet temperature at high-temperature vapor generator. The LCOE and LEIOE present similar trends in most cases, which are most affected by the PAT and GTIT. Finally, a tri-objective optimization is conducted using exergy efficiency, LCOE, and LEIOE as objective functions. Pareto frontier is obtained and the final optimum solution is recommended for engineering practice. Highlights: A new combined cooling and power system is proposed based on dual fuel gas turbine. Thermodynamic, exergoeconomic, and exergoenvironmental analysis are conducted. Levelized cost and environmental impact of exergy are used as evaluation criteria. Optimum economic and environmental indicators are 17.67 /GJ and 3484.90 mPts/GJ. The proposed system is good to balance thermodynamic and environmental performance.